A obra de arte na era da inteligência artificial - Loch, Carolina Valentim (2021)
This work aims to present a critical reflection on the long-standing relationship between art and technology, especially from the moment when artworks are produced with the support of Artificial Intelligence (AI), through Deep Learning. Based on a philosophy of technology, this research intends to meditate on the influence of technology on artistic production throughout the Art History and to reflect its limits in the current moment when artists try to give the machine a task that is not only instrumental, but looking for collaboration for its creation process. With the support of authors, mainly like Ortega y Gasset, Ernst Cassirer, Hannah Arendt, Arlindo Machado and Lucia Santaella, it is provided the meeting of philosophical reflections with thoughts about the symbolic faculty of the human being where appears and orbits the visual arts.